Philo of Alexandria, On the life of Abraham : introduction, translation, and commentary - Birnbaum, Ellen; Dillon, John M.; Philo, of Alexandria (Leiden ; Boston : Brill, 2021)
"On the Life of Abraham displays Philo's philosophical, exegetical, and literary genius at its best. Philo begins by introducing the biblical figures Enos, Enoch, Noah, Abraham, Isaac, and Jacob as unwritten laws. Then, interweaving literal, ethical, and allegorical interpretations, Philo presents the life and achievements of Abraham, founder of the Jewish nation, in the form of a Greco-Roman bios, or biography. Ellen Birnbaum and John Dillon explain why and how this work is important within the context of Philo's own oeuvre, early Jewish and Christian exegesis, and ancient philosophy. They also offer a new English translation and detailed analyses, in which they elucidate the meaning of Philo's thought, including his perplexing notion that Israel's ancestors were laws in themselves"--
General Introduction to the Philo of Alexandria Commentary Series -- Gregory E. Sterling -- Preface -- Abbreviations -- Introduction -- 1 The Place of the Treatise in Philo's Works -- 2 The Place of the Treatise in Philo's Life -- 3 Genre, Aims, and Audience -- 4 Structure, Content, and Exegetical Approaches -- 5 Use and Interpretation of the Bible -- 6 Major Themes -- 7 Intellectual and Cultural Influences -- 8 Previous Scholarship -- 9 Shared and Distinctive Features and Their Implications -- 10 Nachleben -- 11 The Text of the Treatise -- 12 Some Notes on the Method Used in the Translation and Commentary -- Translation: Philo of Alexandria, De Abrahamo -- Part One: Introduction, ʹʹ 1-59 -- Part Two: The Life of Abraham, ʹʹ 60-276 -- Notes to the Text and Translation -- Commentary -- Title of the Work -- Part One: Introduction, ʹʹ 1-59 -- A Prologue, ʹʹ 1-6 -- B The First Triad, ʹʹ 7-47 -- C The Second Triad -- Part Two: The Life of Abraham -- A The Piety of Abraham -- B The Humanity of Abraham, ʹʹ 208-261 -- C Conclusion, ʹʹ 262-276 -- Bibliography -- Index --
Includes bibliographical references and index.
Translated from the original Greek into English.
Online resource; title from digital title page (viewed on September 28, 2020).
eBooks on EBSCOhost
Keywords: Philo, -- of Alexandria; Philo, -- of Alexandria; Abraham -- (Biblical patriarch); Bible. -- Criticism, interpretation, etc; Abraham -- (Biblical patriarch); Philo, -- of Alexandria; Bible; De Abrahamo (Philo, of Alexandria); Criticism, interpretation, etc; Biographies; Biographies